Kajian Literatur Penggunaan Model Pembelajaran Kontekstual Pada Pelajaran IPS SMP - Mohammad Aldiansyah Malik; Sujarwo (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Effective learning is learning that provides the best experience to students in the form of satisfactory results, this is achieved by learning methods that are in accordance with the characteristics of students in general in class. Supported by a good communication relationship between teachers and students so that a good learning environment can be created and later increase students' interest in learning. IPS lessons are the result of the integration of several scientific disciplines, namely economics, history, anthropology, sociology, and geography, the study of IPS is the relationship that occurs between humans and their environment that gives rise to social phenomena. The purpose of this article is to explain and describe contextual learning methods for increasing students' motivation, interest, and achievement in social studies lessons. The method used is the literature study method with SINTA-accredited book sources and journals.